Predicting Vehicle Driver Preference from the Analysis of In-Vehicle Coupon Recommendation Data - Murtada Dohan; Mohammed, Rasha Bashar; Wisam Hazim Gwad; Mohammed Khalaf; Karam M.Z. Othman (Journal of Soft Computing and Data Mining, 2024)
A coupon is a ticket or document used in marketing that may be redeemed for a monetary discount or refund when purchasing a product. The problem, in this case, is to know if a customer will accept a coupon for a particular venue. The answers that the user will drive there ‘right away’ or ‘later before the coupon expires’ are labeled as ‘Y = 1’, and the answers ‘no, I do not want the coupon’ is labeled as ‘Y = 0’. This paper proposes integrating three machine learning techniques to create an ensemble boosting classification (EBC) model for a vehicle coupon recommendation. The algorithms used are k-nearest Neighbor (KNN), Support Vector Machine (SVM), and Decision Tree (DT). The results show that the EBC model surpasses the three machine learning models and achieves the highest performance of accuracy 97.37%, precision 94.14%, recall 96.41%, and F1-score 95.28%.